Techno-Economic Analysis of DME Production from Indonesian Brown Coal: A Preliminary Plant Design - Luthfi, Alif; Nugraha, Mohd Farhan; Ramadhani, Shafira Rachma; Legawati, Lisa; Yolanda, Yogi; Maarasyid, Cici; Zulfansyah, Zulfansyah (Fakultas Teknik UMRI, 2025)
This article presents the preliminary plant design and techno-economic assesment of Dimethyl Ether (DME) production from coal. As the world’s third largest coal producer, Indonesia faces challenges in using low rank lignite due to its high moisture content, wgich limits direct combustion efficiency. The plant was designed to produce 210,000 tons of DME per year, supporting national effort to reduce LPG imports and improve energy security. The calculation include mass and energy balances, equipment sizing, and enviromental considerations suh as CO2 emissions management. Economic evaluation demonstrate project feasibility, with an internal rate of return of 24.28%, a payback period of 3.46 years, and a net present value of 39.60 million USD. Sensitivity analysis shows profitability is highly sensitive to DME price variations. Further research issyngas recommended to develop effective carbon capture strategies and evaluate lifecycle emissions to enhance DME production more enviromentally friendly and sustainable.